Elective induction of labour at 39 weeks in low-risk nulliparous women versus expectant management: a pilot randomized control trial - Aakanksha; Kumari, Archana; Tirkey, Sarita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Elective induction of labor (EIOL) is a debated topic, but recent evidence suggests potential benefits. The ARRIVE trial found that e IOL at 390/7 to 394/7 weeks in low-risk nulliparous women significantly reduced cesarean delivery rates (18.6% vs. 22.2%) and composite perinatal morbidity (4.3% vs. 5.4%).3 This aligns with other studies showing that continuing pregnancy beyond 39 weeks increases maternal/fetal risks. Given that race/ethnicity influences pregnancy duration and outcomes, the current research gap is the lack of specific data on e IOL at 39 weeks in the Indian population Methods: This open-label randomized trial at RIMS, Ranchi (March 2021-October 2022) compared EIOL to Expectant Management (EM) in 60 low-risk nulliparous Indian women (n=30 per group), with the primary outcome being the rate of cesarean delivery. Participants were randomized at 38 weeks and the e IOL group was induced between 39 and 395/7 weeks using dinoprostone/oxytocin. Results: The present randomized, open-label trial conducted on low-risk nulliparous Indian women compared EIOL at 39 weeks with expectant management (EM), analyzing 27 participants in each final group. The primary finding demonstrated that e IOL significantly reduced the Cesarean Delivery rate (37% vs. 66.7% in EM, p=0.038) and led to a shorter postpartum hospital stay. While baseline characteristics were comparable, the EM group developed more complications (e.g., preeclampsia, non-reassuring FHR) leading to higher intervention rates. Although secondary neonatal outcomes (e.g., perinatal death, NICU admission) showed a favorable trend for e IOL, these differences were not statistically significant. Conclusions: This pilot RCT in India found that EIOL at 39 weeks significantly reduced the cesarean delivery rate (33.3% vs. 60% in expectant management, p=0.038), suggesting one CS is avoided per four inductions. EIOL was safe, showing no increase in adverse maternal outcomes (PPH, infection) and even shorter hospital stays, while maintaining positive neonatal outcomes. The study supports EIOL as a safe, effective strategy to lower CS rates in low-resource settings.